Politicized hydrology: Spatial associations among tree-cover loss, protected forests, and hydrometeorological disaster exposure - Miftahul Ardli (Calamity: A Journal of Disaster Technology and Engineering, 2026)
Background: Sumatra has experienced increasing hydrometeorological disaster pressure, particularly floods and landslides, in areas connected to upstream watershed degradation and spatial governance problems. This study examines how disaster distribution, forest conversion discourse, and spatial planning governance interact in shaping flood and landslide risk along the Bukit Barisan corridor. Methods: Using a secondary-data based qualitative-spatial approach, this study analyzes the BIG-BNPB 2025 spatial disaster dataset obtained from the Tanah Air Indonesia geoportal and interprets it through policy documents and scientific literature on watershed degradation, environmental governance, and political ecology. Findings: The results show that hydrometeorological disaster areas are spatially concentrated in Aceh, North Sumatra, and West Sumatra. Based on the compiled disaster polygons, flood areas dominate the observed disaster distribution, reaching approximately 3,980.56 km², while landslide and landslide-prone areas account for approximately 136.95 km² and 556.90 km², respectively. Aceh records the largest total disaster-affected area, reaching approximately 3,119.48 km², indicating a strong concentration of flood risk within upstream-downstream watershed systems. Conclusion: These findings suggest that flood risk in Sumatra should not be interpreted solely as a rainfall-driven natural phenomenon, but also as a governance-related risk amplified by reduced watershed carrying capacity, sedimentation, and weakened ecological control in spatial planning. Novelty/Originality of this article: This study argues that hydrometeorological disasters in Sumatra represent institutionally produced risks when legal and policy instruments fail to protect upstream ecological functions. Strengthening watershed-based policy audits, ecological licensing governance, and stricter control of upstream land conversion is therefore essential for long-term flood and landslide mitigation in Sumatra.